Social Recognition: Experimental Evidence from Blood Donors - Lorenz Götte; Egon Tripodi (Center for Economic Studies and ifo Institute (CESifo), 2022)
Does social recognition motivate prosocial individuals? We run large-scale experiments among members of Italy's main blood donors association, testing social recognition both through social media and peer groups. We experimentally disentangle visibility concerns and peer comparisons, and we study how exposure to different norms of behavior affects giving. In an initial study and two subsequent replications, we find that a simple ask to donate is at least as effective as asks that offer social recognition. A survey experiment with blood donors provides consistent evidence that social recognition backfires when offered to good citizens, as signaling focuses on image motivation. Our results caution against over-reliance on social recognition to promote good citizenship and emphasize the importance of surveying beliefs in the target population to anticipate the outcomes of a policy at scale.
Keywords: 330; prosocial behaviour; blood donations; social recognition; field experiments; social media; WhatsApp